THE EFFECT OF GOALS-CLARITY ON ACHIEVING THE STRATEGIC CLUSTERS: A COMPARATIVE STUDY OF A SAMPLE OF PUBLIC AND PRIVATE UNIVERSITIES - Elaf Mutlaq Hameed; Prof. Dr. Shehenaz Fadhil Ahmed (Scholars Digest Publishing, 2024)
The current study aimed to know the relationship of influence between the clarity of goals as an independent variable and its effect on achieving the dependent variable, i.e. the strategic clusters with their dimensions represented by (regulative procedures, specialized knowledge, logistic support, mobilizing governmental support). The comparative descriptive approach was adopted in analyzing the data. Questionnaire which included (30) items, was also adopted as a tool for measurement and data collection, let alone using personal interviews for a number of members of the sample studied. A purposive sample was chosen for managers at the level of (department, division, unit). It was selected among three public universities represented by (Baghdad, Al-Mustansiriya, Iraqi), and three private ones represented by (Al-Bayan, Al-Farahidi, and Al-Israa) to be the society for the study. The sample size reached (256) directors at the headquarters of the presidencies of the public and private universities selected for the study. A set of statistical methods was relied upon (such as the arithmetic mean, Standard deviation, R value, F value, t value, coefficient of determination R², corrected coefficient of determination R², marginal slope coefficient ß). Using the (SPSS V.25) program, the study reached a number of results, the most important of which was that (the existence of an effect of clarity of goals on strategic clusters). To end with, the study came out with a number of recommendations that serve the purpose for which it was developed.
Keywords: clarity of goals, strategic clusters, public and private universities.